Simulación, análisis, y comparación con CFD del comportamiento de una turbina eólica savonius de rotor liso y rotor modular de 0,2 vatios (2022)
The goal of this project is to simulate a Savonius For this, the numerical calculation software called Startype ve rtical helical wind turbine. CCM+ was used. The performance was sought to be able to compare it from the point of view of aerodynamics with the smooth surface Savonius turbine, as this is the design and construction most commonly found in wind energy conversion platforms. In no case will other types of studies (structural, turbine installation, generation process...) be taken into account. The model of the turbines was created in the SolidWorks softw are and then exported to STAR CMM+ where as much as possible of both models was parameterized. Among the results to obtain, in addition to the performance against the flow, magnitudes such as pressure, torque, speed were found. In addition to other magnitu des related to the simulation (simulation times, memory, number of cells, etc). Finally, it was found that the smoothsurfaced turbine performs better than the one segmented into modules by a considerable margin. This is mainly due to the fact that it is more difficult for the flow to affect the surface of the modular turbine due to the roughness of its material.